Ambiguity Aversion And The Power Of Established Brands - A. V. Muthukrishnan; Luc Wathieu (European School of Management and Technology (ESMT), 2007)
This paper investigates situations where a sizeable sub-set of consumers prefer an inferior (dominated) offer made by an established brand to a superior (dominating) offer made by a less-established brand. Established brands are those for which consumers hold more confident beliefs concerning overall quality. Through a series of eight experiments, we test the hypothesis that the preference for a dominated established brand is linked to ambiguity aversion, a seemingly unrelated pattern of choice behavior between monetary gambles. We first show a correlation between ambiguity aversion and the preference for dominated established brands. We then demonstrate that the preference for established brands is enhanced when ambiguity aversion is made more salient in unrelated preceding choices. To further study the ambiguity-reducing properties of established brands, the last experiments assign brand names to monetary gambles, and it appears that (a priori unrelated) established brand names increase the likelihood of choosing ambiguous gambles. Overall, this research argues that brand equity for longstanding brands derives (at least in part) from consumers' tendency to avoid ambiguity.
urn:nbn:de:101:1-201106143439
Keywords: C91; D10; D80; M31; 650; branding; brand choice; consumer behavior; decision making under uncertainty